2010
DOI: 10.1177/0961203310369681
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to double-stranded DNA-Intermethod comparison between four commercial immunoassays and a research biosensor-based device

Abstract: Patients with systemic lupus erythematosus (SLE) often develop a wide variety of serological manifestations including the presence of antibodies to double-stranded DNA (anti-dsDNA). Positivity for anti-dsDNA constitutes one of the laboratory criteria for the diagnosis of SLE and is therefore clinically relevant. We analyzed the diagnostic accuracies of four commercial anti-dsDNA immunoassays and compared the results with a recently established surface plasmon resonance (SPR) biosensor chip with covalently chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…3,48,49 Consistent with the skin phenotype, the Jak1 S645Pþ/À mice showed a global increase of immunoglobulin isotype levels and autoDNA antibodies in circulation. These features are typical findings in patients with SLE, 50 with a more pronounced increase in females, 51 because we also observed them in female Jak1 S645Pþ/À mice mimicking the human situation.…”
Section: Discussionsupporting
confidence: 52%
“…3,48,49 Consistent with the skin phenotype, the Jak1 S645Pþ/À mice showed a global increase of immunoglobulin isotype levels and autoDNA antibodies in circulation. These features are typical findings in patients with SLE, 50 with a more pronounced increase in females, 51 because we also observed them in female Jak1 S645Pþ/À mice mimicking the human situation.…”
Section: Discussionsupporting
confidence: 52%
“…Various commercial ELISA tests are available through numerous companies. Although based on the same technology, poor agreement can be observed, as seen in previous studies [ 14 , 15 , 19 , 20 ]. Similar to the sensitivity observed for BioPlex 2200 dsDNA in this study, the sensitivity in SLE found for the two ELISAs was lower than previous studies [ 21 , 22 ], indicating that the SLE sample population for this study could be the reason.…”
Section: Discussionmentioning
confidence: 63%
“…As ELISAs are only moderately fast with assay times between 1.5 and 3 hours, the focus has lately shifted towards a decrease in assay time and ease of use. Despite significant technological advances, controversies persist on the method of choice for the detection of these antibodies [ 4 , 14 ]. The BioPlex 2200 dsDNA assay has been compared to other assays (Farr and Farrzyme) in a recent study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROC curves can also be used to compare the diagnostic performance of two or more laboratory or diagnostic tests. A rough guide of AUC for classifying the accuracy of a diagnostic test is the traditional academic point system: 0.90-1 = excellent, 0.80-.090 = good, 0.70-0.80 = fair, 0.60-0.70 = poor, 0.50-0.60 = fail [17,18]. The AUC was 0.940-0.962, when an ROC curve was plotted depending on diagnosis of synovitis based on the thickness of SB and PC, indicating the measurement of the joint capsule with high-resolution ultrasound has a higher power of test and can be viewed as a good evidence for determining modeling success.…”
Section: Discussionmentioning
confidence: 99%